The most important barriers to the development of electromobility in Poland - Sendek-Matysiak, Ewelina (Przegląd Komunikacyjny)
In accordance with the Strategy for Responsible Development, by 2025, over 1 million electric cars powered solely from BEV batteries are to travel on Polish roads [24]. However, although such cars have a number of advantages such as lower maintenance costs, higher acceleration, lower maintenance requirements, lower noise levels than internal combustion cars, and above all no emissions at their place of use, BEV's share in the automotive market remains small and in 2018 year was only 0.1%. Such a marginal number of currently used BEV electric cars in Poland, proves that the electric mobility market is still in the initial phase and its development limits various difficulties. This article discusses the most important barriers to the development of electromobility in Poland related to with the price of buying an electric car, the range of driving on a single charge, infrastructure dedicated to them. Solutions have also been proposed, which should certainly affect the decisions of users when choosing a vehicle with a given type of drive, and consequently the development of electromobility. Keywords: Charging point; Electric vehicle BEV; Electromobility; External costs